(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2023)
Especially in the period after August 2008, when the bursting of the real estate market bubble in the USA developed into a global financial and overall economic crisis, global economic and global social relations in their entirety are permanently facing quite serious unfavorable and crisis situations. It is also true that the factors of those unfavorable and crisis situations have an external genesis and character. That is, all those factors are not strictly financial and economic market factors. For example, the strongly limiting factors of the pandemic and the developments in and around Ukraine. But academically, in no case can and must not bypass or relativize the factors that are internal, market financial and economic factors. In the closest connection with these internal market factors of generation, production and development of unfavorable and crisis situations, especially from the point of view of economic-sociological and political-economic perception, study and understanding, with all its extremely real and objective force and power is imposed the problem of state interventionism, primarily in terms of its impact on overcoming unfavorable and crisis market situations. The fact is that historically, especially in the period starting with the Great Depression (1929-1939) until today, including the collapse of Silicon Valley Bank (2023 year), state interventionism was practically the only factor powerful enough to overcome unfavorable and crisis situations. In the closest connection with this statement, the extremely realistic and objective statement is naturally imposed that the absence of a certain optimal level of scope and quality of the state regulation and supervision of the markets, especially the financial markets, both at the national and global level, has a very strong impact as a factor for the emergence, development and a flare-up of unfavorable and crisis situations in the markets.